Analisis Strategi Pembelajaran Yang Digunakan Oleh Guru IPA Kelas VIII UPTD SMP Negeri 8 Gunungsitoli - Sokhizaro Hulu; Desman Telaumbanua; Novelina Andriani Zega; Hardikupatu Gulo (Departement of Mathematics Education, 2024)
Learning strategy is a learning process planning activity that must be carried out by teachers and students so that learning objectives can be achieved efficiently and effectively. The research objectives are: (1) Describe the learning strategies used by class VIII science teachers at UPTD SMP Negeri 8 Gunungsitoli, (2) Describe the learning activities of class VIII students at UPTD SMP Negeri 8 Gunungsitoli. The type of research used is qualitative research with a descriptive approach. The research location is at UPTD SMP Negeri 8 Gunungsitoli. The research population is class VIII students in the 2024/2025 academic year. Research results: (1) The learning strategies used by class VIII science subject teachers at SMP Negeri 8 Gunungsitoli are expository learning strategies, Contextual Teaching and Learning (CTL) learning strategies, problem-based learning strategies, and cooperative learning strategies. However, what is more dominantly used by science subject teachers is cooperative learning strategies, because the use of cooperative learning strategies is able to actively involve all students in the learning process activities. (2) Students' learning activities during the implementation of learning activities in class VIII of SMP Negeri 8 Gunungsitoli can be demonstrated by students paying attention to the teacher while teaching, students being able to understand the learning material presented by the teacher, students working seriously on the practice questions given by the teacher , students are able to ask questions, students are able to answer questions, students are able to express opinions, students are able to take notes on learning material, and students can make summaries of the material that has been taught. According to the research results, it can be concluded that the strategies used by class VIII science subject teachers at SMP Negeri 8 Gunungsitoli are expository learning strategies, Contextual Teaching and Learning (CTL) learning strategies, problem-based learning strategies, and cooperative learning strategies